Statistical Analysis of the Labor Force of the Arkhangelsk Oblast - Abdullaev Elvin Akhmed oglu (Арктика и Север)
Labor force is a key driver of economic growth and productivity. The more labor force, the more production, trade and services can be created. In addition, the quality and efficiency of the labor force directly affects the level of productivity and competitiveness of the region and countries. Although the workforce is a key resource, managing it can be challenging. One of the main challenges in workforce management is retaining highly qualified employees, as the labor market is constantly changing and opening up new opportunities. This article is devoted to the study of the labor force in the Arkhangelsk Oblast, which is of great importance for understanding the current situation of the region and determining directions for development. The object of the study is the labor force in the specified territory, and the subject is its essence, state, structure and movement. In the course of the study, the following goals were set: determining factors affecting the quality of the labor force, analyzing the dynamics and structure of the labor force, studying the level of employment and unemployment, identifying the impact of the labor force on the economic indicators of the region. The methodological basis of the study is general scientific statistical methods of data analysis: absolute and relative statistical indicators, series of dynamics, correlation and regression analysis. The main conclusion of the article is that the labor force of the Arkhangelsk Oblast is steadily declining, but the balance between the share of men and women in it is preserved. However, the problem of unemployment during the period under review becomes more relevant for women than for men. These changes reflect the need for key measures that will stimulate not only economic development, but also the creation of favorable working conditions.